2015
DOI: 10.1186/s40064-015-0959-x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and morphological variability of shell in populations of Leptinaria unilamellata (d’Orbigny, 1835) (Mollusca, Pulmonata, Subulinidae)

Abstract: BackgroundRecent studies concerning species of land snails have revealed that the shell morphometrics can provide evidence of the differentiation among populations. In many cases, the morphologic analysis combined with the investigation of molecular variability, can support changes in taxonomy of studied groups. In this sense, the study of shell morphometry during snail development can contribute to the understanding of the structural mechanisms that creates the diversity observed.DescriptionThe morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Moreover, increments in the weights, SGR, and shell circumferences could be detected possibly due to their relatively quicker increments as compared to the other growth parameters. This was in concomitant with the report by Medeiros et al, 25 who observed that the growth is mediated through the addition of material from the mantle collar at the shell's opening, nutrient material is continuously added, and growth is therefore first observed at the anterior part of the shell, proceeding onward to the posterior. ANOVA results revealed significant differences in specific growth rates (SGR), shell length increments (SLI), shell circumference increments (SCI), and aperture width increments (AWI) recorded in all five treatments.…”
Section: Relationship Between Extract Concentration and Feed Intake Asupporting
confidence: 87%
“…Moreover, increments in the weights, SGR, and shell circumferences could be detected possibly due to their relatively quicker increments as compared to the other growth parameters. This was in concomitant with the report by Medeiros et al, 25 who observed that the growth is mediated through the addition of material from the mantle collar at the shell's opening, nutrient material is continuously added, and growth is therefore first observed at the anterior part of the shell, proceeding onward to the posterior. ANOVA results revealed significant differences in specific growth rates (SGR), shell length increments (SLI), shell circumference increments (SCI), and aperture width increments (AWI) recorded in all five treatments.…”
Section: Relationship Between Extract Concentration and Feed Intake Asupporting
confidence: 87%
“…In shells without lamellae, deviation is lower than in those that present lamellae. These are intra-population variations of B. schrammi that may be associated with a greater adaptation that some snail species present in the face of environmental adversity (Medeiros et al 2015).…”
Section: Morphological Taxonomymentioning
confidence: 99%
“…The size of the length, width, and height of the gastropod shell are the main indicators to determine its growth and development (Tissot 1984;Chiu et al 2002;Medeiros et al 2015). The results of the analysis of One-Way-ANOVA (Tabel 3) is shown the average of length, width, and height of the shell of M. annulus from each of the stations was significantly different (p<0.05).…”
Section: Difference In Length Width and Height Of Shell Blotch Lenmentioning
confidence: 99%